The Effect of Educational, Escapism, Memorable Tourism Experience on Sustainability-Oriented Loyalty in Kembang Island Park with the Moderating Effect of Biodiversity Knowledge: Green Marketing Perspective - Muhammad Naparin (Asia Marketing Journal)
The biggest challenge of green tourism marketing is to create tourist loyalty based on environment, economy, and socio-cultural sustainability. This study aimed to analyze the influence of educational experience (EDX) and escapism experience (ESX) on memorable tourism experience (MTX), the direct influence of MTX on sustainability-oriented loyalty (SOL), the moderating role of biodiversity knowledge (BIK) on the influence of MTX on SOL, and the direct influence of BIK on SOL. This study used quantitative methods and SmartPLS 4.1 for statistical analysis. The research model was tested on 221 tourists who had visited the Nature Tourism Park situated in the conservation zone. The results showed EDX and ESX significantly affected MTX, MTX and BIK significantly affected SOL, and BIK significantly moderated the influence of MTX on SOL. Originality of this study was to build a model of tourist loyalty that focuses on sustainability with the moderating influence of biodiversity knowledge.